The good research guide : for small-scale social research projects - Denscombe, Martyn (Maidenhead, England : McGraw-Hill/Open University Press, 2010)
This 4th edition offers guidance for success in small scale research projects, with new sections on ethics, Internet research, phenomenology, grounded theory and image-based methods.
Part 1 Strategies for social research: surveys and sampling; case studies; experiments; ethnography; phenomenology; grounded theory, action research, mixed methods -- Part 2 Methods of social research: questionnaires; interviews; observation; documents -- Part 3 Analysis: quatative data; qualitative data; writing up the research -- Frequently asked questions, Research ethics, Data protection, Triangulation, Focus groups.
Previous ed.: 2007.
Includes bibliographical references (p. [359]-365) and index.
Keywords: Social sciences -- Methodology -- Handbooks, manuals, etc; Research -- Methodology